Professional identities of babies early childhood educators - Dinis Monteiro Tadeu, Bárbara Alexandra; Lopes, Amélia (Aprender, 2024)
This article focuses on the study of the perceptions and identity dynamics of babies’ early childhood educators in daycare contexts, conceptually framed within the theory of the construction of professional identities in early childhood education and care and methodologically, as qualitative research, within the interpretative and complexity paradigms, using empirically the techniques of focus groups, interviews, and content analysis. The results indicate that the identity dynamics of the early childhood educators participating in the project depend on processes of negotiation, adaptation, insubordination, submission, or resignation, in which multiple factors come into play – biographical and relational – that contribute, understand, characterize, and impact the construction of professional identities. Understanding the strategies and resources that early childhood educators mobilize to face the challenges of a profession that is under construction and affirming itself may contribute to improving the training of early childhood educators and to the pedagogical action in baby rooms in daycare centres, which has an impact on the education and care of babies, young children, and their families. The social recognition of the importance of these professionals in these contexts may inform educational and organizational policies in the field of early childhood education and care.